ANALISIS PENERIMAAN AUDITOR ATAS DYSFUNCTIONAL AUDIT BEHAVIOR : SEBUAH PENDEKATAN KARAKTERISTIK PERSONAL AUDITOR (STUDI EMPIRIS PADA KANTOR AKUNTAN PUBLIK DI WILAYAH SUMATERA) - Anita, Rizqa; Anugerah, Rita (Jurnal Akuntansi (Media Riset Akuntansi & Keuangan), 2016)
This study aims to examine the personal characteristics of the auditor theacceptance of the auditor on dysfunctional Audit Behavior. More specifically, thisstudy aims to examine the locus of control, the performance auditor, turnoverintention and commitment to the organizations top auditor reception dysfunctionalAudit Behavior. This study uses a survey of the entire public accounting firm inSumatera with a number of respondents as many as 97 respondents. Data analysistools in this study using Structural Equation Modeling-Partial Least Square (PLSSEM)using SmartPLS software Version 2.0 M3. PLS (Partial Least Square). Theresults showed that that the locus of control has positive influence on acceptance ofdysfunctional audit behavior. Auditors performance negatively affect acceptance ofdysfunctional audit behavior. Turnover intention positive influence on acceptance ofdysfunctional audit behavior. Organizational commitment negatively affectacceptance of dysfunctional audit behavior.Keywords: locus of control, the performance auditor, turnover intention andorganizational commitment, and acceptance of the auditor on the auditdysfunctional behavior.